Influence of Water-Repellent Admixtures on the Water-Resistance of Unstabilized and Stabilized Compressed Earth Blocks - J. Alexandre Bogas (International Journal of Architectural Engineering Technology, 2020)
The low durability of water action has been the main issue of earth construction since ancient times. In this way, sustainable solutions are needed to improve the earthen building materials water-resistance performance without significantly changing their appearance and eco-friendly nature. This study aims at characterizing the water-resistance of compressed earth blocks (CEB) produced with or without different types of colorless water-repellent admixtures. To this end, different types of unstabilized and 8% cement stabilized CEB were protected with two post-surface treatments, namely a silane-siloxane based surface water-repellent (SWR) and a natural linseed oil (LO), as well as one olein based integral water-repellent (IWR). Unprotected reference CEB were also considered for comparison purposes. More sustainable CEB were produced with 20% replacement of earth by recycling waste building materials. The CEB were tested in terms of compressive and flexural strength, capillary water absorption, immersion absorption, water permeability, low-pressure water absorption, and water erosion resistance from drip and spray tests. The influence of the moisture content on the compressive strength was also analysed. The cement-stabilization and water-repellent treatments were able to overcome the non-water-resistant nature of unstabilized CEB. In general, the best performance was attained with SWR, followed by IWR. The LO was less effective in reducing the long-term absorption but was able to protect unstabilized CEB from light rainfall simulated conditions. Under severe water erosion, the surface treatments were less effective, but water penetration was reduced up to near 40%. The mechanical strength, total porosity, water permeability and immersion absorption were not significantly affected by water-repellent products. Moreover, the mechanical strength reduction of stabilized CEB after saturation was about 30%, regardless of the water-repellent treatment. The main contribution of water-repellent admixtures occurred in all properties involving capillary absorption.